Novas tecnologias de ensino-aprendizagem: uma análise do poder disciplinar durante as aulas on line, a partir de Michel Foucault uma experiência de ensino remoto no IEMA Pleno em Carutapera – MA. - SILVA, Gilberto de Sousa (2024)
This dissertation addresses new teaching-learning technologies from the perspective of the "Panopticon" concept developed by Michel Foucault. The objective is to analyze how these technologies shape power and surveillance relations in the educational context. The research is being developed at Iema plena in Carutapera - MA, which seeks to make a critical comparison with Foucault's theory of panopticism. A priori, the dissertation explores new teaching technologies, such as online education, digital learning, artificial intelligence and virtual reality, highlighting their growing impact on the educational scenario. Next, the study presents the concept of "Panopticon" proposed by Michel Foucault. Panopticism describes a surveillance model in which a single, centralized observer can monitor a large number of individuals without them knowing when they are being observed. Foucault argues that this structure of surveillance creates a disciplinary environment that shapes people's behavior. The dissertation then establishes a connection between new educational technologies and panopticism. She examines how online platforms, learning management systems, and data analysis tools enable constant supervision of students, both in their academic activities and their online behavior. This raises questions about privacy, student autonomy and the power of educational institutions. Furthermore, it explores how the asymmetry of power between educators and students can be amplified by the use of these technologies, reflecting elements of Foucault's panopticism. In conclusion, the dissertation highlights the importance of balancing the benefits of new teaching technologies with the need to protect students' rights and ensure transparency in surveillance practices. She highlights that, although these technologies can be valuable tools for teaching, it is essential that they are used responsibly and in accordance with ethical principles, so as not to reproduce oppressive power structures similar to the panopticism described by Foucault.